Perkembangan bahasa anak usia dini di era digital: dampak media youtube, peran pengasuhan, dan perubahan sosial - Baitur Rohmah; Thorik Aziz (Jurnal Warna : Pendidikan dan Pembelajaran Anak Usia Dini, 2024)
This study focuses on the impact of YouTube content on early childhood language development in the digital era, highlighting the roles of parenting and social change. The research background is the increasing dominance of YouTube as an educational platform for children, potentially influencing their cognitive and linguistic development. The aim of this study is to explore how exposure to YouTube content affects children's language development, and to analyze the roles of parenting and social change dynamics in this process. The research method employed is a descriptive qualitative approach, with data collected through participatory observation, in-depth interviews with parents and teachers, and analysis of digital content frequently accessed by children. The results indicate that educational content on YouTube can enrich vocabulary, enhance grammar comprehension, and support children's speaking abilities, provided the content is of high quality and consumed in a controlled manner. However, excessive exposure to YouTube content can lead to negative effects, such as the introduction of inappropriate words and a decrease in social interaction. This study also found that the role of parenting, including content selection, screen time management, and involvement in discussions, is crucial in maximizing benefits and minimizing negative impacts of digital media. The conclusion of this research emphasizes the need for balance in the use of digital technology and the importance of parenting in ensuring that digital experiences support children's overall language development and social skills.